CHEMOTHERAPEUTIC EFFICACY OF TRIDHAM AND 1,2,3,4,6-PENTA-O-GALLOYL-Î²-DGLUCOSE ON ANTIOXIDANTS STATUS AND TUMOR MARKERS IN EXPERIMENTAL MAMMARY CARCINOMA IN SPRAGUE-DAWLEY RATS - Dharmalingam, Karthick; Ramakrishnan, Stalin; Panchanatham, Sachidanandam; Palanivelu, Shanthi (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: To study the restorative effect of Tridham (TD) and 1,2,3,4,6-penta-o-galloyl-Î²-D-glucose (PGG) on 7,12-dimethyl benz(a)anthracene (DMBA)-induced mammary carcinoma in female Sprague-Dawley rats. Methods: Rats were divided into seven groups of six animals each. Group I rats served as control. Group II - mammary carcinoma was induced by DMBA. Group III and Group IV were induced with DMBA and subsequently treated with TD and PGG, respectively, for 48 days. Group V was treated with DMBA and subsequently with a standard drug, cyclophosphamide (CYC). Group VI and Group VII were given TD and PGG alone, respectively, for 48 days. After the experimental period, the levels of lipid peroxides (LPO), activities of enzymic and non-enzymic antioxidants such as superoxide dismutase, catalase, glutathione peroxidase, glutathione-S-transferase, reduced glutathione, vitamin C, and vitamin E were evaluated in the breast tissue of control and experimental rats. Levels of LPO, marker enzymes such as 5'-nucleotidase and lactate dehydrogenase, were also evaluated. Results: The levels of enzymic and non-enzymic antioxidants were decreased in DMBA-induced rats when compared to control rats. The levels of tumor markers were increased in DMBA-induced rats when compared to control rats. These parameters were restored to near normal levels on treatment with TD and PGG. Conclusions: The results suggest that TD and PGG have a cytoprotective role in DMBA-induced breast cancer-bearing rats. The effect of TD and PGG was found to be more pronounced than CYC, a standard drug. Keywords: Breast cancer, Tridham, Penta galloyl glucose, Antioxidants, Tumor markers, Sprague-Dawley rats.